(3QSGdI aj GdcGahQs - (3CHh Ydj CMeO Hf YHO GdQMef, GHf efOhjg GdCUagGfj,J (B372 (3g` s
(3ChdgG (B:s
(3dMb eG bjd dh ScJ ef dGjYde dSbW GdGNJdGa hPdc Gf GdGNJdGa ai GdTF GfeG jMOK ef Jcde GdLGgd ajg HeG dGjYdeg XGfG Gf bO Ydeg s
(3BNQgG (B:s
(3aUGQ dPdc GdcGahQ ai GdZGjI GdbUhi Ydi bWY GdHGg hJYWjd BdGJgG agPG eG MVQfi ef Gdbhd ai GdcGahQ hGddg hdi GdJhajb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B885s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1538) s
Keywords: (3GdWHs